Optimizing Optical Attocells Positioning of Indoor Visible Light Communication System - Mohammed S. M. Gismalla, Mohammed S. M. Gismalla; Asrul I. Azmi, Asrul I. Azmi; Mohd R. Salim, Mohd R. Salim; Farabi Iqbal, Farabi Iqbal; Mohammad F. L. Abdullah, Mohammad F. L. Abdullah; Mosab Hamdan, Mosab Hamdan; Muzaffar Hamzah, Muzaffar Hamzah; Abu Sahmah M. Supa’at, Abu Sahmah M. Supa’at (Tech Science Press, 2023)
Visible light communication (VLC), which is a prominent emerging solution that complements the radio frequency (RF) technology, exhibits the potential to meet the demands of fifth-generation (5G) and beyond technologies. The random movement of mobile terminals in the indoor environment is a challenge in the VLC system. The model of optical attocells has a critical role in the uniform distribution and the quality of communication links in terms of received power and signal-to-noise ratio (SNR). As such, the optical attocells positions were optimized in this study with a developed try and error (TE) algorithm. The optimized optical attocells were examined and compared with previous models. This novel approach had successfully increased minimum received power from −1.29 to −0.225 dBm, along with enhanced SNR performance by 2.06 dB. The bit error rate (BER) was reduced to 4.42 × 10−8 and 6.63 × 10−14 by utilizing OOK-NRZ and BPSK modulation techniques, respectively. The optimized attocells positions displayed better uniform distribution, as both received power and SNR performances improved by 0.45 and 0.026, respectively. As the results of the proposed model are optimal, it is suitable for standard office and room model applications.